Engaging torture survivors in the global fight against torture - Soley, Berta (Torture Journal, 2021)
Lived experience can be emancipating and also paralysing, but foremost, it is immensely valuable to combat what has been suffered in first person (Henry, 2021). How to recognise that contribution and engage torture survivors in the global fight against torture? What role do survivors play in society? How to involve survivors in advocacy and policy-making processes? What are the existing power (in)balances at play? Who gets to decide whether a survivor should speak up or not? Acknowledging that it can prompt some organisational, therapeutic, and professional considerations, what are the limits? How do we ensure that the survivor’s well-being is protected along the process? To what extend should survivors be engaged in our organisation’s decision-making? In front of the current on-going debate on the need of actively engaging torture survivors in the global fight against torture, IRCT held a webinar to explore this topic. The webinar examined torture survivor engagement in the rehabilitation process of rebuilding lives, seeking justice and torture prevention. This article summarises the discussion held during the webinar with the presentations from Léonce Byimana[1], Feride Rushiti[2], Kolbassia Haoussou[3] and Vasfije Karsniqi-Goodman[4] and further inputs from other IRCT-members. [1] Executive Director of Torture Abolition and Survivors Support Coalition (TASSC) [2] Executive Director of the Kosova Rehabilitation Center for Torture Victims (KRCTV) [3] Director of Survivor Empowerment at Freedom From Torture [4] Survivor and member of the Kosovan parliament